Death anxiety among women with breast cancer at the National Center for Radiotherapy and Nuclear Medicine in Khartoum - Ali, Soha Mohamed; Eltahir, Elrasheed Ismaeil (Journal of Educational and Psychological Sciences, 2021)
This study addressed death anxiety among women with breast cancer at the National Center for Radiotherapy and Nuclear Medicine in Khartoum, in order to identify: differences in death anxiety among women with breast cancer according to the variable of performing mastectomy at the Center. Where They used the descriptive method with a sample size 35 women with breast cancer were chosen by the intentional method at the Center, they applied the death anxiety scale on the patients, the data was analysed statistically using statistical package for the social sciences (SPSS). They reached a number of conclusions and recommendation, including: The death anxiety among women with breast cancer at the Center is high, there are statistically significant differences between death anxiety among women with breast cancer at the Center according to the variable of performing mastectomy in favor of those who underwent a mastectomy. Guidance should be offered to the family and especially the husband to how to deal with his injured wife according to her stage and accept the apparent negative emotions and behaviors, and encourage her to express herself.
Keywords: Anxiety Death; Infected; Breast Cancer; Death